Establishment of driteria, preservation and utilization of lina in the production of puto sulot - Villanueva, Katrina L. (2009.)
Puto sulot is a fried flour-coconut based product from Barili, Cebu which traditionally uses lina (freshly-gatheres tuba or coconut sap without baluk) as starter.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Lina; Puto sulot